2020
DOI: 10.1111/gbb.12708
|View full text |Cite
|
Sign up to set email alerts
|

The circadian geneCryptochrome 2influences stress‐induced brain activity and depressive‐like behavior in mice

Abstract: Cryptochrome 2 (Cry2) is a core clock gene important for circadian regulation. It has also been associated with anxiety and depressive‐like behaviors in mice, but the previous findings have been conflicting in terms of the direction of the effect. To begin to elucidate the molecular mechanisms of this association, we carried out behavioral testing, PET imaging, and gene expression analysis of Cry2−/− and Cry2+/+ mice. Compared to Cry2+/+ mice, we found that Cry2−/− mice spent less time immobile in the forced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Cry2 is crucial for normal emotional behavior and is directly associated with anxiety-like behavior [ 82 ] and as mentioned earlier, mice with higher anxiety behavior exhibit lower expression levels of Cry2 in the hippocampus in comparison with normal mice [ 50 ]. Moreover it has been found that ELF-EMF (50–60 Hz) can disturb circadian biorhythms by perturbation of the clock function of cryptochromes [ 83 ]; however, we did not find any significant Cry 2 alteration in any of the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cry2 is crucial for normal emotional behavior and is directly associated with anxiety-like behavior [ 82 ] and as mentioned earlier, mice with higher anxiety behavior exhibit lower expression levels of Cry2 in the hippocampus in comparison with normal mice [ 50 ]. Moreover it has been found that ELF-EMF (50–60 Hz) can disturb circadian biorhythms by perturbation of the clock function of cryptochromes [ 83 ]; however, we did not find any significant Cry 2 alteration in any of the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety-related behavioral tests are often performed together with depression tests in mouse models of neuropsychiatric disorders since anxiety usually co-morbids with depression (Cryan and Mombereau, 2004;Millstein and Holmes, 2007;Krishnan and Nestler, 2011;Jung et al, 2014;Belovicova et al, 2017;Sokolowska et al, 2021). Several behavioral tests based on the conflict between competing behaviors of exploring novel environments and avoiding potential threatening situations have been validated to assess anxiety, including the elevated plus maze (Pellow et al, 1985;Lister, 1987), open field (Treit and Fundytus, 1988), and light/dark box (Crawley and Goodwin, 1980;Crawley, 1981;Blumstein and Crawley, 1983), where our previous studies revealed sex differences in the open field and elevated plus maze tests with female C57BL/6N and FVB/N mice being less anxious (Eltokhi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since anxiety-related behavioral tests are often performed together with depression tests in mouse models of neuropsychiatric disorders (Cryan and Mombereau, 2004;Millstein and Holmes, 2007;Krishnan and Nestler, 2011;Jung et al, 2014;Belovicova et al, 2017;Sokolowska et al, 2021), we extended our study and investigated sex differences in an anxiety test, the hyponeophagia test. Consistent with our previous study revealing sex differences in other anxiety tests in adolescent mice (Eltokhi et al, 2020), female C57BL/6N and DBA/2 mice showed an increased latency to drink the diluted milk compared to male mice at P27 (Trial 1: C57BL/6N: P = 0.006, DBA/2: P = 0.041 FVB/N: P = 0.99; Trial 2: C57BL/6N: P = 0.014, DBA/2: P = 0.027, FVB/N: P = 0.55; Figure 4A and Table 2).…”
Section: Anxiety-related Hyponeophagia Test At P27 and P37mentioning
confidence: 99%
“…Cryptochromes are key proteins for the circadian clock 532 and SCN's intercellular networks development, which subserves coherent rhythm expression 533 . Furthermore, it is also shown that cryptochrome is associated with bipolar disorder disease [534][535][536][537] . In the context of animal magnetoreception, cryptochromes are the canonical magnetic sensing proteins (See Section 3.4) 44 , with flavin radicals playing a key role.…”
Section: Lithium Effects On Hyperactivitymentioning
confidence: 99%